A systematic and theoretical approach to the marketing of higher education - Rabenu, Edna; Shkoler, Or (Frontiers in Psychology, 2022)
The aim of this article was to open a hatch to the consumer psychology research through the eyes of Facet Theory. The Facet Theory enables to delve into a concept or an issue under investigation and define it formally, systematically, and comprehensively, but still parsimoniously. In order to better explain its philosophical basis and the principles of this theory, we apply and demonstrate it on the domain of marketing of higher education to students. There are four distinct facets identified in this regard, namely, (A) Achieving Personal Goals, (B) Institution’s Marketing Orientation, (C) Secondary Decision Criteria, and (D) Level of Education. Based on those facets and their related respective elements, a suggested definitional directive for the marketing of higher education to students is construed.